2013
DOI: 10.3390/ijms14010888
|View full text |Cite
|
Sign up to set email alerts
|

HGF–MET Cascade, a Key Target for Inhibiting Cancer Metastasis: The Impact of NK4 Discovery on Cancer Biology and Therapeutics

Abstract: Hepatocyte growth factor (HGF) was discovered in 1984 as a mitogen of rat hepatocytes in a primary culture system. In the mid-1980s, MET was identified as an oncogenic mutant protein that induces malignant phenotypes in a human cell line. In the early 1990s, wild-type MET was shown to be a functional receptor of HGF. Indeed, HGF exerts multiple functions, such as proliferation, morphogenesis and anti-apoptosis, in various cells via MET tyrosine kinase phosphorylation. During the past 20 years, we have accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
47
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 118 publications
(182 reference statements)
3
47
0
Order By: Relevance
“…Although the inhibitory mechanisms of PHA-665752 are different for each cell type, PHA-665752 generally regulates morphogenic differentiation, cell survival, and motility by inhibiting p-AKT and p-ERK, and suppresses anchorage-independent growth of gastric, lung, and glioma cancer cell lines (4,6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the inhibitory mechanisms of PHA-665752 are different for each cell type, PHA-665752 generally regulates morphogenic differentiation, cell survival, and motility by inhibiting p-AKT and p-ERK, and suppresses anchorage-independent growth of gastric, lung, and glioma cancer cell lines (4,6).…”
Section: Discussionmentioning
confidence: 99%
“…However, de novo resistance to these TKIs occurs because of c-MET amplification or HGF overexpression (20)(21)(22). c-MET overexpression contributes to tumor development via crosstalk between other receptors, such as EGFR, HER2, and HER3 (4,21). Moreover, overexpression of HGF stimulates c-MET activation which trans-phosphorylates other receptors (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10] The binding of HGF to c-MET triggers the recruitment of the Grb2-SOS and Gab-1 proteins, leading to the activation of numerous signaling pathways, including Ras-ERK, PI3K/AKT, PLC, Shp-2, and Crk-2, which play important roles in cell proliferation, morphogenesis, and motility. 11 Although involved in important physiologic functions, overexpression of HGF and mutations in c-MET have been reported in some events related to malignant behavior including reduced cell-cell contact, activation of epithelial mesenchymal transition, increased tumor angiogenesis, and enhanced cellular survival. 11,12 Clinical trials examining the targeted inhibition of the HGF/c-MET circuitry have demonstrated improved outcomes for patients with different types of solid tumors.…”
mentioning
confidence: 99%
“…11 Although involved in important physiologic functions, overexpression of HGF and mutations in c-MET have been reported in some events related to malignant behavior including reduced cell-cell contact, activation of epithelial mesenchymal transition, increased tumor angiogenesis, and enhanced cellular survival. 11,12 Clinical trials examining the targeted inhibition of the HGF/c-MET circuitry have demonstrated improved outcomes for patients with different types of solid tumors. 13,14 Very few studies have examined the role of the HGF/ c-MET pathway in SGTs.…”
mentioning
confidence: 99%